2020
DOI: 10.1111/jbi.13796
|View full text |Cite
|
Sign up to set email alerts
|

Do bigger bodies require bigger radiators? Insights into thermal ecology from closely related marine mammal species and implications for ecogeographic rules

Abstract: Aim:The aim of this study was to determine if marine mammals follow ecogeographic rules. We examined Bergmann's rule and Allen's rule in two pilot whale species with contrasting latitudinal distributions. Location: Northwest Atlantic Ocean.Taxon: Globicephala spp. Methods:We analysed morphometric data collected from strandings of short-and long-finned pilot whales in the Northwest Atlantic Ocean to assess intraspecific and interspecific variation in surface area to volume ratios (SA:V) of the body core and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…These were used to derive Equation 2. Flippers and flukes account for another 11% of the total body surface area, but are equipped with counter‐current vascular heat exchange systems capable of reducing heat losses to negligible levels (Adamczak et al, 2020; Elsner et al, 1974; Scholander & Schevill, 1955), so the surface areas of these appendages are not included in estimates of the area insulated by blubber. Body mass (M b ; equivalent to body volume) is a function of both L b and maximum body girth (G max ) and is described by Equation 3 (Sumich et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were used to derive Equation 2. Flippers and flukes account for another 11% of the total body surface area, but are equipped with counter‐current vascular heat exchange systems capable of reducing heat losses to negligible levels (Adamczak et al, 2020; Elsner et al, 1974; Scholander & Schevill, 1955), so the surface areas of these appendages are not included in estimates of the area insulated by blubber. Body mass (M b ; equivalent to body volume) is a function of both L b and maximum body girth (G max ) and is described by Equation 3 (Sumich et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…For most mammals, the use of ventilatory characteristics to estimate metabolic rates can be confounded by the dual roles of their respiratory surfaces that function simultaneously as sites for gas exchange while providing extensive surfaces for evaporative cooling during periods of heat stress. Unlike terrestrial mammals, however, cetaceans regulate heat losses with vascular radiators in flukes, flippers, and other specialized body surfaces (Adamczak et al, 2020; Elsner et al, 1974; Scholander & Schevill, 1955), and the relative simplicity of their ventilation mechanics is expected to more closely reflect their rates of gas exchange and O 2 utilization (Piscitelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ontogenetic patterns in body composition revealed that mature dolphins were leaner, and body composition was less variable as dolphins reached maturity (Figure 5). Mature dolphins are larger with lower surface area to volume ratios, which would improve their capacity to retain heat, reducing the need for thicker blubber (Worthy and Edwards, 1990;Noren and Wells, 2009;Adamczak et al, 2020). In contrast, as young dolphins are smaller, they have thicker, more insulative blubber to compensate for the additional thermoregulatory costs of being small (McLellan et al, 2002;Dunkin et al, 2005;Koopman, 2007;Montie et al, 2008;Noren and Wells, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of NEFOP and ASM data agreed with this assessment; any pilot whale bycatch identified to the species level consisted exclusively of long-finned pilot whales, and morphological measurements and habitat assessments indicated that observed pilot whales were long-finned pilot whales. For example, all adult female pilot whales that were taken as bycatch were greater than 400 cm in length, and a recent study of pilot whale morphometrics from the eastern seaboard of the United States indicated that mature female short-finned pilot whales are considerably less than 400 cm in length (mean 358.48 ± 4.26 cm for mature female short-finned pilot whales and 432.81 ± 5.82 cm for mature female long-finned pilot whales, respectively 32 . Further, stock assessment reports delineate short- and long-finned pilot whales based on sea surface temperature, with the probability of a pilot whale being a long-finned pilot whale of near 1 at water temperatures < 22 °C 49 ; see also results of this study), and all observations of pilot whale bycatch occurred in temperatures below 22 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cooler water species typically have lower surface area to volume ratios in their body core, and blubber with a higher lipid content, lower conductivity, and increased fatty acid stratification 30 , 31 . The larger appendages of long-finned pilot whales in comparison to short-finned pilot whales may reflect the need for enhanced mechanisms of heat dissipation in the large, well-insulated long-finned species, which occurs in cooler waters 32 .…”
Section: Introductionmentioning
confidence: 99%